2016
DOI: 10.3389/fnhum.2016.00104
|View full text |Cite|
|
Sign up to set email alerts
|

Positive and Negative Symptoms in Schizophrenia Relate to Distinct Oscillatory Signatures of Sensory Gating

Abstract: Oscillatory activity in neural populations and temporal synchronization within these populations are important mechanisms contributing to perception and cognition. In schizophrenia, perception and cognition are impaired. Aberrant gating of irrelevant sensory information, which has been related to altered oscillatory neural activity, presumably contributes to these impairments. However, the link between schizophrenia symptoms and sensory gating deficits, as reflected in oscillatory activity, is not clear. In th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 73 publications
3
17
0
Order By: Relevance
“…For example, Leicht et al (2010) investigated auditory evoked gamma band oscillations in SCZ and found a significant reduction of power in SCZ compared to HC around 50 ms after stimulus presentation. Keil et al (2016) recently replicated this effect. Another study by Lenz et al (2011) examined evoked gamma band responses in SCZ during an auditory oddball-paradigm and reported diminished responses to standard and deviant stimuli in SCZ around 40 to 90 ms after stimulus onset.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…For example, Leicht et al (2010) investigated auditory evoked gamma band oscillations in SCZ and found a significant reduction of power in SCZ compared to HC around 50 ms after stimulus presentation. Keil et al (2016) recently replicated this effect. Another study by Lenz et al (2011) examined evoked gamma band responses in SCZ during an auditory oddball-paradigm and reported diminished responses to standard and deviant stimuli in SCZ around 40 to 90 ms after stimulus onset.…”
Section: Discussionmentioning
confidence: 81%
“…It might be that the absence of significant main effects between groups relates to a lack of statistical power. Indeed, previous studies have reported diminished evoked beta band (13–30 Hz) and gamma band (>30 Hz) oscillations in SCZ (Gallinat et al, 2004; Leicht et al, 2010, 2015; Lenz et al, 2011; Keil et al, 2016). For example, Leicht et al (2010) investigated auditory evoked gamma band oscillations in SCZ and found a significant reduction of power in SCZ compared to HC around 50 ms after stimulus presentation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, Heed and colleagues2 recently suggested that oscillatory brain activity seems to be optimally suited for implementing the transformation and integration of multiple coordinates. Interestingly, there is now plenty of evidence associating altered spontaneous brain oscillations with risk for psychosis6061626364, as well as abnormal multisensory perception in schizophrenia6566. Future research is warranted to determine a direct relationship between abnormal touch remapping and altered oscillatory brain activity in schizotypy.…”
Section: Discussionmentioning
confidence: 99%
“…Thoma et al () and Smith et al () reported specific relationships between M50 gating and symptoms in schizophrenia, and others did so for P50 gating and symptoms (Arnfred & Chen, ; Erwin, Turetsky, Moberg, Gur, & Gur, ; Louchart‐de la Chapelle et al, ; Ringel et al, ; Yee, Nuechterlein, Morris, & White, ). In spectral analysis of a traditional EEG sensory gating paradigm, Keil and colleagues (Keil, Roa Romero, Balz, Henjes, & Senkowski, ) reported that SZ had less gamma‐band power reduction from S1 to S2, which correlated with Positive and Negative Syndrome Scale (PANSS) positive symptoms, and less alpha‐band phase coherence reduction from S1 to S2, which correlated with PANSS negative symptoms. These two spectral measures of gating were in turn correlated.…”
Section: Introductionmentioning
confidence: 99%